2015
DOI: 10.2495/ut150321
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the institutional environment on public–private partnership transport projects

Abstract: Public-private partnerships (PPP) have become a key tool in the provision and management of transport infrastructure projects providing countries access to the necessary financial resources for infrastructural needs. Despite the increasing number of PPP projects implemented in many countries, there are factors that hinder development of these projects. One of these factors is the weakness of the institutional environment, particularly in developing countries. To date, few empirical studies have analysed the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…According to Niekerk, Ruiter, Mcwabeni, Kruger, and Grinker (), the successful implementation of PPPs demands a relatively high level of administrative capacity from the structure that assumes overall contractual control of the process. Pérez‐D'Ole, Castro, Herraiz, and Carpintero () indicate that institutions are key to creating an investment climate where competence is feasible and that the implementation of PPP projects in a country depends on the existence of high‐level public sector capacity, corporate governance, transparency and law enforcement and contractual rights, control of corruption, and appropriate regulatory framework.…”
Section: Challenges Of Ppps In Ghanamentioning
confidence: 99%
“…According to Niekerk, Ruiter, Mcwabeni, Kruger, and Grinker (), the successful implementation of PPPs demands a relatively high level of administrative capacity from the structure that assumes overall contractual control of the process. Pérez‐D'Ole, Castro, Herraiz, and Carpintero () indicate that institutions are key to creating an investment climate where competence is feasible and that the implementation of PPP projects in a country depends on the existence of high‐level public sector capacity, corporate governance, transparency and law enforcement and contractual rights, control of corruption, and appropriate regulatory framework.…”
Section: Challenges Of Ppps In Ghanamentioning
confidence: 99%
“…(2015) asserted that quality of regulation is a determinant of PPP investment in ports that attracts private bidders and the market competitiveness of the ports, while Baker (2016) documented that regulatory quality has a positive impact on PPP private investor markets irrespective of the level of uncertainty in the exchanged environment. Pérez-D'Oleo et al. (2015) found that countries with sound regulatory quality attract a reasonable proportion of investment through PPP projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Osei-Kyei and Chan (2019) insisted that rampant corruption is one of the reasons for transportation projects failure across Nigeria, Mozambique and South Africa. Countries that attract a large proportion of investment in PPP projects may likely have zero tolerance for corruption (Pérez-D'Oleo et al. , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Government performance, regulatory quality and corruption control also affect investment, but to a lesser extent. Countries that have improved the quality of regulation and control over corruption over time tend to have higher levels of investment [26]. The transparency of the work of state authorities, the efficiency of administrative and legal mechanisms, the absence of bureaucratic obstacles and the minimization of corruption influences can significantly reduce the individual risks of PPP projects.…”
mentioning
confidence: 99%